THE EFFECT OF TEACHER’S BASIC TEACHING SKILL TOWARDS STUDENTS' ACHIEVEMENT OF SMP N 28 MERANGIN - Boma Prima Kasmi; Ade Taufan (Dinasti International Journal of Education Management And Social Science, 2019)
This research is motivated by the lack of basic skills in teaching teachers at SMP Negeri 28 so that the learning done by the teacher is not optimal and results in student learning outcomes that are not as expected. The purpose of this study was to determine how much influence the basic teaching skills of teachers on integrated social studies learning outcomes of students of Merangin 28 Middle School. Kec. Batang Masumai. Kab. Merangin. This study uses a quantitative approach with survey methods. Based on the results of Simple Regression siq value 0.003 <0.05, and a simple regression equation ? = 19.890 + 0.541x, Ho is rejected and Ha is accepted that there is a significant influence between the basic skills of teaching teachers on learning outcomes. Based on the Determination Coefficient is 23.6% this result shows that as much as 23.6% of learning outcomes are influenced by the basic skills of teacher teaching. The remaining 76.4% is influenced by factors. So it can be concluded that there is a significant influence on the basic skills of teaching teachers on integrated social studies learning outcomes of SMP Negeri 28 Merangin students in the 2017/2018 school year.